Model Volatilitas Return Index Saham Syariah Indonesia Melalui Pendekatan Bayesian Markov Switching GARCH - Afnanda, Afridho; Maiyastri, Maiyastri; Devianto, Dodi (Lattice Journal : Journal of Mathematics Education and Applied, 2024)
Volatility is an important aspect of financial analysis that plays a crucial role in risk management and investment decision making. Modeling the volatility of financial asset prices is challenging due to its dynamic and complex nature. One approach used to address this problem is the GARCH model. In volatility problems, there is a tendency for structural changes in more complex data so that the GARCH model cannot be used, to overcome this, the Markov Switching GARCH (MS-GARCH) model is used to overcome the problem of changing the data structure. Furthermore, the Bayesian model is also used in combination with the MS-GARCH model to overcome the small sample size. This research uses Indonesia Sharia Stock Index (ISSI) return data from January 1, 2023 to December 31, 2023. From the comparison of the Akaike Information Criterion (AIC) and Bayesian Information Criterion (BIC) values to see the best model for forecasting ISSI data, the best model in forecasting ISSI data is the Bayesian MS-GARCH model with the smallest AIC value of -252.544 and BIC value of -237.0894, compared to the MS-GARCH model the AIC value is smaller than the Bayesian MS-GARCH model of -251.1048 and its BIC is -235.6502.   Volatilitas merupakah salah satu aspek penting dalam analisis keuangan yang memainkan peran krusial dalam manajemen resiko dan pengambilan keputusan investasi. Pemodelan volatilitas harga aset keuangan menjadi suatu tantangan karena sifatnya yang dinamis dan kompleks. Salah satu pendekatan yang digunakan untuk mengatasi masalah ini adalah model GARCH. Pada masalah volatilitas kecenderungan terjadinya perubahan struktur pada data yang lebih kompleks sehingga tidak bisa digunakan model GARCH, untuk mengatasi hal ini digunakan model Markov Switching GARCH (MS-GARCH) untuk mengatasi masalah perubahan struktur data. Selanjutnya digunakan juga model Bayesian yang dikombinasikan dengan model MS-GARCH untuk mengatasi jumlah sampel yang kecil. Penelitian ini menggunakan data return Index Saham Syariah Indonesia (ISSI) dari tanggal 1 Januari 2023 hingga 31 Desember 2023. Dari hasil perbandingan nilai Akaike Information Criterion (AIC) dan Bayesian Information Criterion (BIC) melihat model terbaik untuk meramalkan data ISSI, diperoleh model terbaik dalam meramalkan data ISSI adalah model Bayesian MS-GARCH dengan nilai AIC yang terkecil yaitu sebesar -252,544 dan nilai BIC yaitu -237.0894, dibandingkan pada model MS-GARCH nilai AICnya lebih kecil dibandingkan model Bayesian MS-GARCH sebesar -251,1048 dan BIC nya sebesar -235.6502.